1995
DOI: 10.3168/jds.s0022-0302(95)76639-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Neutral Detergent Fiber Concentration and Forage Source on Performance of Lactating Cows

Abstract: 'Mott' dwarf elephantgrass, forage sorghum, 'Tifton 81' bermudagrass, and whole corn plant were stored as silage and fed as the only forage source in diets formulated to 31, 35, and 39% NDF. The 12 diets were fed for ad libitum intake as a TMR to midlactation Holstein cows, primarily to determine the effect of NDF concentration and forage source on DMI and milk production. Increased dietary NDF concentration linearly decreased DMI (3.69 to 3.35%) and OM intake (3.39 to 3.06%) as a percentage of BW and linearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
1
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 11 publications
5
19
1
4
Order By: Relevance
“…Data in Table 1 indicate that the wall cell fractions, aNDFom and ADFom, were lower for the BMR hybrid but the Lignin(sa) fraction was higher (+2%). Other studies have observed no difference in ADF and NDF concentrations between conventional and BMR-sorghum [9] [15]. It must be said, that the BMR sorghum was not compare to its correspondent normal one (the same genotype without the mutation) and so, the effect of the specific mutation is confounded with hybrid.GE content was not significant different between sorghum types.…”
Section: Forage Characteristics and In Vivo Digestibility Of Sorghum mentioning
confidence: 94%
“…Data in Table 1 indicate that the wall cell fractions, aNDFom and ADFom, were lower for the BMR hybrid but the Lignin(sa) fraction was higher (+2%). Other studies have observed no difference in ADF and NDF concentrations between conventional and BMR-sorghum [9] [15]. It must be said, that the BMR sorghum was not compare to its correspondent normal one (the same genotype without the mutation) and so, the effect of the specific mutation is confounded with hybrid.GE content was not significant different between sorghum types.…”
Section: Forage Characteristics and In Vivo Digestibility Of Sorghum mentioning
confidence: 94%
“…Similarly, Thorstesson et al (1992) observed a greater concentration of NDF for conventional sorghum when compared with its bmr-6 or bmr-18 counterparts. However, other studies have observed no difference in ADF and NDF concentrations between conventional and bmr-6 sorghum (Ruiz et al, 1995;Aydin et al, 1999). A review of bmr research by Cherney et al (1991) indicated considerable variation exists in fiber composition among conventional and bmr sorghum hybrids.…”
Section: Silage and Dietary Compositionmentioning
confidence: 99%
“…When forage alone is fed to sheep or cattle, NDF is negatively correlated with dry matter intake (Osbourn et al, 1974; Reid et al, 1988). When forage is fed together with concentrates, NDF is negatively correlated with dry matter intake if the rumen capacity of the animal is not reached (Conrad et al, 1964; Mertens, 1987; Ruiz et al, 1995). Thus, it is desirable to reduce NDF of forages.…”
mentioning
confidence: 99%